72.2k views
3 votes
Find the sum of the first 6 terms of 3 - 6 + 12 + …

Find the sum of the first 6 terms of 3 - 6 + 12 + …-example-1

1 Answer

3 votes

Answer:


S_6 = -63

Explanation:

The sequence above is a geometric sequence.

The common ratio (r) =
(-6)/(3) = (12)/(-6) = -2

The common ratio < 1, therefore, the formula for the sum of nth terms of the sequence would be:
S_n = (a_1(1 - r^n))/(1 - r)

a1 = 3

r = -2

n = 6

Plug in the values into the formula


S_6 = (3(1 - (-2^6))/(1 - (-2))


S_6 = (3(1 - (64))/(1 + 2)


S_6 = (3(-63))/(3)


S_6 = -63

User Mazzaroth
by
5.7k points